Acute effects of transcranial direct current stimulation on cycling and running performance. A systematic review and meta-analysis. Issue 2 (1st February 2022) - Shyamali Kaushalya, Fernando; Romero-Arenas, Salvador; García-Ramos, Amador; Colomer-Poveda, David; Marquez, Gonzalo
Abstract: Transcranial direct current stimulation (tDCS) has been proven to induce positive effects on athletic performance. The present study aimed to analyse the effect of anodal-tDCS on endurance (time to exhaustion [TTE] or endurance time trial [ETT]) and sprint performance during cycling and running tasks. We performed a systematic literature review in the databases Medline (via PubMed), SPORTDiscus and Science Direct. We included only randomised controlled trials conducted with healthy individuals in which an anodal-tDCS protocol was applied prior to cycling or running tests. The effect of anodal-tDCS (experimental condition) was compared against sham stimulation (control condition). A total of 15 interventions from 13 studies were included. The sub-group analysis revealed a positive effect of anodal-tDCS on TTE (standardised mean differences [SMD] = 0.37; 90% confidence interval [CI] = 0.13, 0.61; p  = 0.01), but not on ETT (SMD = 0.00; 90% CI = −0.29, 0.30; p  = 1.00) or sprint performance (SMD = 0.19; 90% CI = −0.23, 0.60; p  = 0.46). The current meta-analysis suggests that the effect of anodal-tDCS on whole-body dynamic exercises (running and cycling) could be task dependent. Specifically, anodal-tDCS enhance running and cycling time to exhaustion performance during TTE tasks but not ETT or sprint tasks. The increase in cortical excitability induced by anodal-tDCS may lead to lower ratings of perceived exertion by reducing the input required to perform the physical task. Task should be taken into account, because it is probably influencing the result obtained by anodal-tDCS.